Two-Phase Anaerobic Digestion of Municipal Organic Solid Wastes - Rodríguez-Pimentel, R.; Ramírez-Vives, F.; Jesús-Rojas, A. de; Martinez-Valdez, F. J.; Rodríguez-Pérez, S.; Monroy-Hermosillo, O. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Two stages anaerobic digestion of the organic fraction of municipal solid wastes (OFMSW) is proposed using a batch anaerobic trickling bed (BATB) reactor in the first hydrolysis and acidogenesis stage. At total solids loading of 135 g/L and reaction times around 30 days, total solids (Î·TS) and chemical oxygen demand (Î·COD) removal efficiencies above 46% were obtained independently of pH (between 4.1 and 6.4). Dependent on pH were methane production, four times more at pH 6.4 than at 4.8 and four times more volatile fatty acids (VFA) production at 6.4 than at 4.1 and twice than at 4.8. Leachates generated in the BATB reactor were diluted with municipal wastewater and fed to an upflow anaerobic sludge blanket (UASB) reactor at volumetric organic loading rates from 11 to 28 g/L.d where 90% COD removal efficiencies (Î·COD) and 11.4 g CODCH4./L.d were obtained. Two stages anaerobic digestion results in high rates of solids removal and methane production (0.63 kWhr/kg TS fed).